Assess and engage: How Poll Everywhere can make learning meaningful again for millennial library users. Issue 2 (3rd April 2019) - Deng, Liya
Abstract: Millennial learning is heavily dependent on the use of mobile technologies for information gathering, processing, and sharing. This project examines how student response systems, such as Poll Everywhere, impact the effectiveness of information literacy instruction in a mid-size academic library. Data collected from Millennial student participants in 26 instructional sessions indicate that such systems are effective in measuring students' familiarity with library resources and preferences in information use. The results also demonstrate how the integration of Poll Everywhere encourages classroom discussion, reduces redundancy in instruction, and helps make learning more meaningful for Millennial students.